Digital Financial Innovation as a Strategic Driver of MSMEs’ Financial Performance - Rani Arifah Normawati; Eko Esti Santoso; Ika Rachmawati (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
This study explores the impact of Digital Financial Innovation (DFI) on the financial management capabilities and performance of Micro, Small, and Medium Enterprises (MSMEs) in East Java Province. Employing a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS), the research investigates how DFI influences four factors of financial management: liquidity planning, lender management, customer management, and financial strategy, and how these factors subsequently affect financial performance. The findings reveal that DFI significantly enhances all four financial management factors, demonstrating its role as a catalyst for modernizing MSMEs’ financial operations. Among these factors, lender management, customer management, and financial strategy exhibit a positive and significant effect on financial performance, highlighting the importance of managing external relationships and leveraging strategic financial planning. In contrast, liquidity planning does not show a direct impact on performance, suggesting that access to digital tools alone is insufficient without strategic application. Notably, financial strategy emerges as the most influential factor, emphasizing that MSMEs benefit most from DFI when they adopt data driven and forward-looking decision-making approaches. Overall, this study positions DFI as a strategic enabler that not only strengthens financial management capabilities but also drives financial performance in the digital economy. The results offer practical insights for MSME managers and policymakers seeking to promote financial innovation as a pathway to long-term business sustainability.